Canva-based instructional design for strengthening students’ digital literacy skills - Widayati, Iis (Science Center Group, 2025)
Background: Digital literacy has become an essential competency in contemporary education due to the increasing integration of technology in classroom learning. Despite this demand, many students continue to experience difficulties in evaluating information, creating digital content, and communicating effectively through visual media. Instructional innovation that integrates multimodal digital tools is therefore required to address these challenges. Canva-based instructional design offers a structured visual-digital learning environment that may strengthen students’ digital literacy skills through interactive and collaborative activities. Objective: This study aimed to examine the effectiveness of Canva-based instructional design in strengthening students’ digital literacy skills in formal classroom settings. Methods: The study employed a quasi-experimental design with a pre-test and post-test control group approach involving 56 junior secondary students divided into experimental and control groups. The experimental group received structured Canva-based instructional activities, while the control group received conventional instruction. Data were collected using a validated digital literacy skills test and classroom observation instruments. Statistical analyses included independent samples t-test, paired samples t-test, normalized gain (N-gain), and Cohen’s d effect size to determine statistical and practical significance. Results: The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (p < 0.001). The experimental group demonstrated a moderate-to-high N-gain (0.69), whereas the control group showed low-to-moderate improvement (0.31). The calculated effect size (d = 1.48) indicated a large educational impact. Classroom observations further confirmed increased student engagement, improved visual communication competence, and enhanced collaborative digital performance in the experimental group. Conclusion: Canva-based instructional design significantly enhances students’ digital literacy skills by promoting multimodal engagement, collaborative learning, and creative digital production. The findings support the integration of structured visual-digital instructional strategies to strengthen digital literacy development in contemporary education environments.